Escoamento superficial em rampas cultivadas com Capim Marandu no tratamento de efluente da suinocultura - Milen, Larissa Cabral (2019)
The technique of surface runoff on ramps cultivated with grasses is an alternative for the treatment of effluents, especially those of domestic and agricultural origin, in cases where the construction of conventional treatment plants is not accessible. It